Performance of titaniumânickel (Ti/Ni) and graphite felt-nickel (GF/Ni) electrodeposited by Ni as alternative cathodes for microbial fuel cells - Satar, I. (Taiwan Institute of Chemical Engineers, 2018)
Electrodes are important components of bioelectrochemical systems (BESs), such as the microbial fuel cells (MFCs). The low-cost cathodes of titaniumânickel (Ti/Ni) and graphite felt-nickel (GF/Ni) are important to be evaluated as cathodes for MFCs. In this study, Ni particles are deposited onto the Ti and GF surface using a simple and low-cost electrodeposition technique. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) were used to analyse the cathode surfaces. The electrodeposition of Ni onto GF appears more uniform without significant agglomeration compared with that onto Ti. This uniform deposition is perhaps the reason for a higher maximum power density (Pmax), lower internal resistance (Rin) and higher Columbic efficiency (CE) for MFC with GF/Ni cathode (113.4 Â± 0.6 mW/m2, 1264.4 Î© and 29.6, respectively) than those measured with Ti/Ni cathode (110.7 Â± 8.0 mW/m2, 3375.8 Î© and 23.7, respectively). However, the performance of these cathodes remains lower compared with the GF/Pt cathode (140.0 mW/m2, 845.7 Î© and 42.0, respectively). Based on the preparation technique, material cost and performance, both Ti/Ni and GF/Ni cathodes can be considered as alternative to Pt catalyst for MFC application. Â© 2018 Taiwan Institute of Chemical Engineers